The Use of Clinical Scores in the Management of Immune Thrombocytopenic Purpura in Children - Roşu, Vasile Eduard; Spoială, Elena-Lia; Roşu, Tamara Solange; Ivanov, Anca-Viorica; Mocanu, Adriana; Munteanu, Alecsandra; Lupu, Vasile Valeriu; Miron, Ingrith; Gavrilovici, Cristina (Frontiers in Pediatrics, 2022)
Abstract: While the majority of children with recently diagnosed ITP have a benign, self-limiting condition, most often with a spontaneously recovery, 40% of children with ITP progress towards persistent ITP and 10% - 20% goes towards chronicity. Several clinical scores have been developed with the aim to perform a better monitoring outcome or to differentiate transient versus persistent ITP (e.g. Donato score). Our paper aims to describe and to compare the most important scores used in the management of ITP in children: bleeding severity scores and chronicity prediction scores. These scores include a combination of different already known risk factors: age, gender, presence of a previous infections or vaccination, bleeding grade, type of onset, platelet count at diagnosis. The real utility of these scores has been a matter of debate and no consensus has been reached so far as to their necessity to be implemented as compulsory tool in the care of children with ITP.